Haemorrhoidal artery ligation versus rubber band ligation for the management of symptomatic second-degree and third-degree haemorrhoids (HubBLe): a multicentre, open-label, randomised controlled trial - Brown, Steven R.; Tiernan, James P.; Watson, Angus J.M.; Biggs, Katie; Shephard, Neil; Wailoo, Allan J.; Bradburn, Mike; Alshreef, Abualbishr; Hind, Daniel (Elsevier, 2016)
Background